(3ebGdI GdEScfOQ GdEaQhOjSi aj Gdchf hCi TF gh Ydi QCi CQSWhWGdjSs - (3GdGScfOQ GdGaQhOjSjs
(3ChdgG (B:s
(3bGd GdEScfOQ (B: (3Ef CQSWhWGdjS MO Gdchf MOkG bGFekG s
(3BNQgG (B:s
(3JeJ ebGdI GdEScfOQ GdEaQhOjSi ai Gdchf hCi TF gh Ydi QCi CQSWhWGdjS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(798/3) s
Keywords: (3GdadSaI hGdefWbs